1997
DOI: 10.1159/000213835
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Erythrocyte Anion Transporter Protein, Band 3, as a Marker for Alzheimer’s Disease: Structural Changes Detected by Electron Microscopy, Phosphorylation, and Antibodies

Abstract: Band 3, a ubiquitous membrane transport, regulatory, and structural protein, is represented in brain by at least 4 isoforms. Bands 3 in brain performs the same functions as it does in erythrocytes (RBC). It is susceptible to oxidative damage, which, ultimately, terminates its life and that of the cell. We examined the changes band 3 undergoes in Alzheimer’s disease (AD) because our previous studies suggest that band 3 is a pivotal protein in neurological disease. Because we hypothesize that AD is a total body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…This suggested that band 3 existed in normal neurons in, predominately, an unaltered or uncleaved state; and that degradation of band 3 occurred in AD, thus allowing binding of antibodies to pep‐COOH. In other studies, antibodies to band 3 and its peptides bound to structures in AD but not normal brain, as determined by immunoelectron microscopy 100,101. (Reproduced from Saitoh et al 64 with permission.)…”
Section: Senescent Cell Antigen and Anti‐band 3 Antibodies In Diseasesmentioning
confidence: 92%
“…This suggested that band 3 existed in normal neurons in, predominately, an unaltered or uncleaved state; and that degradation of band 3 occurred in AD, thus allowing binding of antibodies to pep‐COOH. In other studies, antibodies to band 3 and its peptides bound to structures in AD but not normal brain, as determined by immunoelectron microscopy 100,101. (Reproduced from Saitoh et al 64 with permission.)…”
Section: Senescent Cell Antigen and Anti‐band 3 Antibodies In Diseasesmentioning
confidence: 92%
“…Moreover, Band 3 (AE1) , an anion exchanger transmembrane protein ,which is important for organizing the structure of the red blood cells (RBC) membrane, which performs the same functions in brain as it does in erythrocytes (RBC) and which is phosphorylated by PKC, showed similar alteration in brain and RBC of AD patients. These parallel changes included decreased 32P-phosphate labeling, altered conformation of band 3 recognized by polyclonal and monoclonal antibodies and decreased anion transport in RBC (Kay and Goodman, 1997). This finding could suggest that one of the sources of this alteration of a major transport complex in two different cell types is either a general modification in PKC activity or changes in the membrane bilayer, which is stabilized by Band 3 in RCB.…”
Section: Pkc In Blood Cellsmentioning
confidence: 89%
“…The normal lifespan of band 3 correlates with the lifespan of the cell (6,19,20,22,24,25). The breakdown of band 3 and the accumulation of SCA on cells triggers removal of that cell (6,8,9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Therefore, band 3 is an excellent marker protein for posttranslational modifications during aging and, perhaps, disease.…”
Section: Discussionmentioning
confidence: 99%
“…To date, our aging studies indicate that the anion transport ability of band 3 decreases in brains and erythrocytes from old mice (10,19,(23)(24)(25)(26)(27). This decreased transport ability precedes obvious structural changes such as band 3 degradation and generation of SCA (10,19,23,(20)(21)(22)(23)(24)(25)(26)(27) and occurs concommitantly with generation of aged/altered band 3.…”
Section: Discussionmentioning
confidence: 99%